2021
DOI: 10.1111/jade.12344
|View full text |Cite
|
Sign up to set email alerts
|

Productive Uncertainty: The Pedagogical Benefits of Co‐Creating Research in the Design Studio

Abstract: Balancing the competing demands of research and teaching has long been lamented by academics. The challenges associated with Covid‐19 will make this increasingly difficult. An integrated approach to research and teaching, where students are directly engaged in the production of research, may provide a useful strategy to support ongoing research within the design disciplines whilst befitting student learning. The production of original research requires a willingness to engage in – and manage –uncertainty. Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Not all uncertainties are desirable all the time. Previous research has theorized distinctions between desirable and undesirable uncertainty in classrooms using different language (e.g., desirable and undesirable difficulties; Bjork & Bjork, 2011; productive and unproductive uncertainty, McLaughlan et al, 2021; good and bad uncertainty, Beghetto, 2017). In the current position paper, Weaver's (1949) concepts of “desirable uncertainty” and “undesirable uncertainty” are adapted to differentiate between resources and opportunities to improve students' understanding from noise, irrelevance, and inappropriate information transmission.…”
Section: Desirability Of Scientific Uncertainty: How Are Scientific U...mentioning
confidence: 99%
“…Not all uncertainties are desirable all the time. Previous research has theorized distinctions between desirable and undesirable uncertainty in classrooms using different language (e.g., desirable and undesirable difficulties; Bjork & Bjork, 2011; productive and unproductive uncertainty, McLaughlan et al, 2021; good and bad uncertainty, Beghetto, 2017). In the current position paper, Weaver's (1949) concepts of “desirable uncertainty” and “undesirable uncertainty” are adapted to differentiate between resources and opportunities to improve students' understanding from noise, irrelevance, and inappropriate information transmission.…”
Section: Desirability Of Scientific Uncertainty: How Are Scientific U...mentioning
confidence: 99%
“…The results indicated that both the 5E teaching model and previous learning experiences contributed to students' conceptual learning in mechanics. Using instructor observations and student feedback, the literature [10] critically reflects on a studio model that was iteratively refined over the course of two semesters with the intent to intentionally exacerbate the complexity already present in the pedagogy to generate new knowledge. A set of strategies were outlined to enable students to manage this uncertainty to ensure that this was beneficial to student learning.…”
Section: Introductionmentioning
confidence: 99%
“…Innovating the teaching and training system and training standards of the environmental art design profession can realize the cross-fertilization of the discipline of environmental art design profession with the scientific and technological revolution and industrial change, and the cross-fertilization of the professional curriculum with multidisciplinary knowledge [4][5][6][7]. Oriented by the all-media perspective, which aligns with the ability cultivation requirements of the environmental art design profession, it can give full play to the teaching advantages of project-based teaching and make teaching the environmental art design professional courses more targeted [8][9].…”
Section: Introductionmentioning
confidence: 99%